ANALYSIS OF UNEMPLOYMENT BY INDIVIDUAL CHARACTERISTICS: THEORETICAL ORIGINS AND REVIEW OF THE LITERATURE - Ouerghemmi, Wafa (International Journal For Research In Business, Management And Accounting, 2021)
The main objective of the analysis of unemployment by individual characteristics is to answer the following question: what makes two job seekers with the same level of education, the same diploma and the same sex not do not have the same chances of finding a job? The answer lies in the individual characteristics that affect their job search trajectories. These individual characteristics (or data) differ from person to person. They can be observed as, for example, age, sex, region ... or not observed as "psychological" factors, which are not identifiable, but exist and affect the probabilities of exiting unemployment.